The potential benefits and trade-offs of using sub-surface water retention technology on coarse-textured soils: Impacts of water and nutrient saving on maize production and soil carbon sequestration - Nkurunziza, Libère; Chirinda, Ngonidzashe; Lana, Marcos A.; Sommer, Rolf; Karanja Ng'ang'a, Stanley; Rao, Idupulapati M.; Romero Sánchez, Miguel Antonio; Kuyak, Shem; Quintero, Marcela; Lewu, Francis; Joel, Abraham; Nyamadzawo, George; et al. (Frontiers Media, 2019)
In Sub-Saharan Africa, several smallholder communities continuously grapple with soil-based poverty as the coarse-textured soils on which they eke out a living have low water and nutrient retention capacities. The new sub-surface water retention technology (SWRT), is based on the subsurface installation of impermeable water‐retaining membranes of linear and low-density polyethylene, reduces the amount of water and nutrients lost through deep percolation especially on coarse-textured soils. In this study, we used stochastic simulations on the diffusion of sub-surface water retention technology (SWRT) on coarse-textured (sandy) soils in eight different Eastern and Southern African countries. Using results from previous research on SWRT we estimated increases in maize grain yields and biomass accumulation. Results from the least and most promising diffusion scenarios suggested that with ten years of widespread adoption of SWRT regional maize production could increase by 10 and 40 million tonnes per season. Carbon sequestration could reach 2 to 4 tonnes from the 7th year after implementation (YAI) and 2 to 12 tonnes for the 15 YAI for the best diffusion scenario as consequence of increased biomass production following SWRT adoption. While our results suggest synergistic reductions in the rate of water and nutrient loss from crop root zones, SWRT is characterized by high initial financial and labour investment costs without effective financial support would be prohibitive to uptake by the generally resource-limited smallholder farmers working on sandy soils. Moreover, as SWRT is new, there is a need for more dissemination efforts to increase awareness on the technologies amongst extension workers, decision-makers and agricultural investors that can promote and incentivize the adoption of this technology in areas were agricultural productivity is constrained by coarse-textured soils.